2020
DOI: 10.1128/jvi.00900-20
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Simplex Virus Organizes Cytoplasmic Membranes To Form a Viral Assembly Center in Neuronal Cells

Abstract: Herpes simplex virus (HSV) is a neuroinvasive virus that has been used as a model organism for studying common properties of all herpesviruses. HSV induces host organelle rearrangement and forms multiple, dispersed assembly compartments in epithelial cells, which complicates the study of HSV assembly. In this study, we show that HSV forms a visually distinct unitary cytoplasmic viral assembly center (cVAC) in both cancerous and primary neuronal cells that concentrates viral structural proteins and is a major s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 91 publications
(115 reference statements)
1
28
0
Order By: Relevance
“…Assembly of viruses in eukaryotes typically occurs in defined subcellular compartments referred to as assembly factories or virus assembly centers (VACs) [1, 10]. For example, many eukaryotic viruses complete their final assembly at the plasma membrane, where high concentrations of viral proteins accumulate before being incorporated to form the mature virion.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Assembly of viruses in eukaryotes typically occurs in defined subcellular compartments referred to as assembly factories or virus assembly centers (VACs) [1, 10]. For example, many eukaryotic viruses complete their final assembly at the plasma membrane, where high concentrations of viral proteins accumulate before being incorporated to form the mature virion.…”
Section: Resultsmentioning
confidence: 99%
“…Subcellular organization is an important trait in all domains of cellular life, allowing cells to carry out their myriad required functions faithfully and efficiently, and also plays a key role in the replication of viruses [1-4]. Upon infection of a host cell, many eukaryotic viruses manipulate host proteins and components of various organelles such as the Golgi apparatus and endoplasmic reticulum to form replication factories in which they can safely and efficiently replicate their genomes [5-9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, the vAC had been thought to represent a unique structure associated with HCMV infection that was not described in other herpesviruses (25). However, a recent study showed that herpes simplex virus 1 (HSV-1) forms juxtanuclear assembly compartments similar to the HCMV vAC in primary mouse neurons and human neuron-derived cells, but not in fibroblasts or epithelial cells (26). Although not essential for virion production, vAC formation has been shown to be necessary for efficient HCMV virion assembly and maturation.…”
mentioning
confidence: 99%